In- Vitro Studies on the Antioxidant Activity and Pharmacological Properties of Ciassampelos Pariera L.: Life Sciences -Botany - Elavarasan, P; Muruganantham, A.; Ambikapathy, V.; Babu, S.; Panneerselvam, A.; Kanmani, A.; Prakash, P (International Journal of Life Science and Pharma Research, 2023)
The current investigation stated that the antioxidant properties of Cissampelos pareira L. leaf extract of medicinal plants are a rich resource of ingredients that can be used in drug development for human life. The medicinal plant Cissampelos pareira with different solvents such as aqueous, acetone, ethanol, and methanol performed different concentrations like 100, 200, 300, 400, and 500μg/ml were carried out by three methods such as hydrogen peroxide scavenging (H2O2), DPPH and thiobarbituric acid assay. As per the antioxidant properties of C. pareira an aqueous extract of hydrogen peroxide scavenging (H2O2) showed the highest percentage of activity compared to the other methods of antioxidant. The minimum rate of antioxidant properties of DPPH in the C. pareira with 500 μg/ml in high activities than the low concentration. According to the acetone extracts of C. pareira leaf, the maximum percentage of inhibition in hydrogen peroxide scavenging (H2O2) whereas low percentages of inhibition by thiobarbituric acid activity at 500 μg/ml concentration, respectively. Although the extraction solvent ethanol reaction is a concern, the same trend of results of antioxidant properties of hydrogen peroxide scavenging (H2O2) assay showed excellent properties and minimum in thiobarbituric acid was found to be recorded with a maximum concentration of 500 μg/ml respectively. According to the methanolic extract of C. pareira leaf exhibited maximum antioxidant properties at 500μg/ml concentration and minimum percentage of activity at thiobarbituric acid, activity was found to be recorded respectively. Among the three methods, hydrogen peroxide scavenging (H2O2) showed excellent antioxidant activity compared with other methods and ascorbic acid as a standard. Antioxidant activities play a significant role in pharmacological functions because of bioactive ingredients. However, there are some health problems due to the deficiencies of macronutrients that establish an effective manner. This research article describes the current status of the world’s herbal medicinal products and properties suggestions for facilitating C. pareira was better tomorrow in humanity.